Sistemas bidimensionais formados por silício e germânio: um estudo de primeiros princípios - Rupp, Caroline Jaskulski (2015)
First principles calculations within the density functional theory have been used to study the main structural, energetic, electronic, and optical properties of hydrogenated Si and Ge in the 2D structures (silicane and germanane). The calculations of the energetic stability were performed using the GGA-PBE approximation for the exchange-correlation functional. To a better description of the electronic properties, the HSE06 functional was used. We obtain that silicane and germanane are semiconductors com energy band gap of 2.94 eV (indirect, where the VBM is localized in the Γ point while the CBM is localized in the M point) and 1.61 eV (direct, both VBM and CBM are localized in the Γ point), respectively. The analysis of optical properties shows that germanane has a direct and smaller band gap being superior to silicane for fotocatalysis using solar energy. However, considering the production of H2 and O2 from the water splitting both materials are suitable only to the water reduction. The chemical functionalization through the substitution of a H atom by a N, P, S, Li, Na, K, Mg and Ca atom do not change the geometric structure of silicane and germanane. The calculated binding energies show that N, P and S adsorbed on a H site have greater binding energies (greater stability) when compared to alkaline metals (Li, Na, and K) and alkaline earth metals (Ca and Mg). The results show that the chemical functionalization give rise to new electronic levels inside the band gap, which is decreased when compared to the pristine system. Compared to the GGA-PBE functional, the use of HSE06 gives great values for the band gap as well as for the work function. A trend between the binding energies and the work functions is observed, the greater the binding energy the greater the work function. We also considered the chemical doping when a boron or a nitrogen substitutes a Si or Ge atoms. We have observed that when a B substitutes a SiH (GeH) unit, the systems preserve the semiconductor properties with a localized and empty electronic level inside the band gap. The adsorption of a H atom on the B site decreases the formation energies and the systems present metallic (for high concentrations of B) or p-type semiconductor (for low concentrations of B) properties. When a second H atom is adsorbed on the B atom the systems are more stable (lower formation energies) and semiconductors properties are observed. For N substituting a SiH (GeH) unit the semiconductor properties are preserved, however the band gap decreases and for silicane the band gap changes from indirect (pristine system) to direct (both VBM and CBM are localized in the Γ point). When a H atom is adsorbed on the N atom the systems present metallic (for high concentration of N) or n-type semiconductor properties (for low concentration of N). When a second H atom is adsorbed on the N impurity the systems present semiconductor properties, but localized electronic levels are present in the band gap. The analysis of the charge density and the electronic density of states shows that these localized levels come from Si (Ge) atoms with dangling bonds. The adsorption of H atoms on the dangling bonds stabilize the systems, which present negatives values for the formation energies (the systems are exothermic). These results show that the hydrogenated Si and Ge in the 2D structures are excellent candidates to be used in many applications, such as, fotocatalysis and electronic devices.